Elevated levels of serum PCSK9 in male patients with symptomatic peripheral artery disease: The CAVASIC study. (January 2021) - Kheirkhah, Azin; Lamina, Claudia; Rantner, Barbara; Kollerits, Barbara; Stadler, Marietta; Pohlhammer, Johannes; Klein-Weigel, Peter; Fraedrich, Gustav; Kronenberg, Florian
Abstract: Background and aims: Peripheral artery disease (PAD) affects more than 200 million people worldwide. Increased low-density lipoprotein cholesterol (LDL-C)levels are a risk factor for PAD and the concentrations are influenced by proprotein convertase subtilisin/kexin type 9 (PCSK9). PCSK9 regulates the recycling of the LDL receptors to the cell membrane surface. Only a limited number of mostly small studies investigated the association between serum PCSK9 concentrations and PAD of different definition, which revealed contrasting results. Methods: Serum PCSK9, lipoprotein(a) [Lp(a)] and other lipoprotein concentrations were measured in male participants of the CAVASIC study, a case-control study of 248 patients with intermittent claudication and 251 age and diabetes-matched controls. Results: PAD patients had significantly higher PCSK9 concentrations when compared to controls (250 ± 77 vs. 222 ± 68 ng/mL, p  < 0.001). Logistic regression analysis with adjustment for age revealed that an increase in PCSK9 concentrations of 100 ng/mL was associated with a 1.78-fold higher risk for PAD (95%CI 1.38–2.33, p  = 1.43 × 10 −5 ). The association attenuated, but was still significant when adjusting additionally for age, Lp(a)-corrected LDL cholesterol, HDL cholesterol, high-sensitivity-CRP, statin treatment, hypertension, diabetes mellitus and smoking (OR = 1.49, 95%CI 1.03–2.18, p  = 0.035). The strongest association was observed when both PCSK9 concentrations were above the median and Lp(a) concentrations were above 30 mg/dL (OR = 3.35, 95%CI 1.49–7.71, p  = 0.0038). Conclusions: Our findings suggest an association of higher PCSK9 concentrations with PAD, which was independent of other lipid parameters and classical cardiovascular risk factors. Graphical abstract: Image 1 Highlights: Few small studies investigated the association between PCSK9 levels and peripheral artery disease (PAD), with contrasting results. We measured PCSK9 and Lp(a) levels in 248 patients with intermittent claudication and 251 matched controls. PAD patients had significantly higher PCSK9 levels compared to controls. Association was independent of other cardiovascular risk factors. The strongest association was observed with PCSK9 > median and Lp(a) > 30 mg/dL.